2003
DOI: 10.1097/01.lab.0000067498.89585.06
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Cell–Derived Factor-1 from Biliary Epithelial Cells Recruits CXCR4-Positive Cells: Implications for Inflammatory Liver Diseases

Abstract: SUMMARY:Although stromal cell-derived factor-1 (SDF-1) plays an important role in hematopoiesis in the fetal liver, the role after birth remains to be clarified. We investigated the role of SDF-1 and its receptor, CXCR4, in 75 patients; this included controls and patients with viral hepatitis, liver cirrhosis, primary biliary cirrhosis, primary sclerosing cholangitis, and autoimmune hepatitis. Interestingly, SDF-1 appeared up-regulated in biliary epithelial cells (BEC) of inflammatory liver disease. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
90
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 41 publications
3
90
0
Order By: Relevance
“…We demonstrate that oval cells synthesize SDF-1, as shown by in situ hybridization and by immunohistochemistry. Stromal cell-derived factor-1 immunolabeling has already been demonstrated in cholangiolar cells in a variety of human chronic liver diseases 28 and in biliary ductal plate epithelial cells during development. 22 However, in the latter study, it was not clear whether SDF-1 was synthesized by labeled cells or if it was of exogenous origin and bound to cell surface receptors or to plasma membrane-associated heparan sulfates.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that oval cells synthesize SDF-1, as shown by in situ hybridization and by immunohistochemistry. Stromal cell-derived factor-1 immunolabeling has already been demonstrated in cholangiolar cells in a variety of human chronic liver diseases 28 and in biliary ductal plate epithelial cells during development. 22 However, in the latter study, it was not clear whether SDF-1 was synthesized by labeled cells or if it was of exogenous origin and bound to cell surface receptors or to plasma membrane-associated heparan sulfates.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Chemokines also are expressed on pathological bile ducts. 10,11 For ex-ample, Terada et al 12 reported that stromal-derived factor 1 expressed on bile ducts is responsible for the migration and recruitment of lymphoid cells in portal tracts and around bile ducts in primary biliary cirrhosis (PBC) as well as in chronic viral hepatitis (CVH). Although the upregulation of fractalkine and CX3CR1 expression has been reported in hepatic parenchyma and bile ductules of hepatitis C virus-infected livers, 13 their expression and immunopathological significance remain unexplored in normal and pathological bile ducts.…”
mentioning
confidence: 99%
“…5 Finally, with injury, immunohistochemical data demonstrate robust CXCL12 expression by proliferating bile ductules in all forms of liver injury, and biliary CXCL12 expression is further supported by the accumulation of CXCR4-positive lymphocytes in the periportal region. 2,6 A careful review of the literature, however, reveals that most data supporting BEC expression of CXCL12 are based on immunohistochemistry using a single monoclonal CXCL12 antibody (murine anti-human/mouse CXCL12, clone 79018). We believe that differentiated BECs may not express CXCL12 and that the observed pattern of BEC expression is a result of antibody crossreactivity to an epitope found in BECs.…”
mentioning
confidence: 99%
“…Herein, we show that despite previous studies demonstrating robust CXCL12 expression by BECs, their role in hepatic CXCL12 production may be more limited. 2,6,8 …”
mentioning
confidence: 99%